Observer‐based formation tracking control for leader–follower multi‐agent systems. Issue 2 (10th January 2019) - Zhao, Wei; Yu, Wenwu; Zhang, Huaipin
Abstract : This study investigates the formation tracking control for second‐order leader–follower multi‐agent systems. To estimate the velocity and acceleration of the leader, distributed observers are constructed for each follower. Based on the observed states, the authors propose a novel distributed formation tracking control protocol and analyse two communication networks with and without communication delays. Then, they prove that each agent can follow the active leader closely and form the desired spatial pattern. Finally, simulation examples are provided to show the validity of the theoretical results.